Association between blood lipid level and embryo quality during in vitro fertilization. Issue 13 (March 2020) - Wang, Shanshan; Wang, Jun; Jiang, Yiqun; Jiang, Weihua
Abstract : Abstract: The aim of this study was to investigate the relationship between blood lipid level and the parameters of embryo morphology of in vitro fertilization (IVF). A total of 488 patients undergoing conventional IVF were divided into pregnant (n = 286) and nonpregnant (n = 202) groups. Levels of triglycerides (TG), total cholesterol (TC), high-density lipoproteins (HDL), low-density lipoprotein (LDL), lipoprotein (a), lipoprotein (b), and embryo outcomes were studied. Spearman correlation was performed to analyze the correlation between blood lipid levels and embryo quality in pregnant group. The normal fertilization rate and number of good quality embryos were higher than nonpregnant group ( P  < .05). TG, TC, and LDL levels were negatively correlated with number of normal fertilized oocytes, while TG, TC, and Lp(b) were negatively correlated with number of good quality embryos. TG level was negatively correlated with number of oocytes and cleavage embryos while HDL and Lp(a) were positively correlated with number of oocytes, normal fertilized oocytes and cleavage embryos ( P  < .05). TG, TC, LDL, and Lp(b) levels had negative correlation with embryo quality, while HDL and Lp(a) had positive correlation with the embryo quality. Our present findings showed blood lipid levels may provide certain reference for the prediction of IVF pregnancy outcome.